Analysis of the efficiency and sustainability of the underground loop in Hangzhou Future Science and Technology City - Huajin Zhang; Qifeng Yu (PLoS ONE, 2026)
In order to improve the low utilization efficiency and limited environmental benefits of the underground loop in Hangzhou Future Science and Technology City, this study systematically analyzes the operation status of the loop road by collecting traffic flow data through field research and combining questionnaire interviews to understand the driver’s experience. It is found that the current underground loop system faces several challenges, including low public awareness, insufficient precision in traffic guidance, inconsistent management of land parcel access interfaces, limited operational flexibility, and inadequate realized carbon reduction. As a result, only about 10% of traffic uses the loop for arrival and departure, and the utilization of underground transportation resources remains far below the expected target. Based on the comparative analysis of similar projects such as Xidong New City in Wuxi and Zhenru Subcenter in Shanghai, this study proposes strategies such as constructing a comprehensive four-tier traffic guidance system, strengthening intelligent information management and control, unifying the collaborative management standards of parcel access interfaces, and deepening low-carbon and sustainable operation. These strategies can effectively alleviate surface-level traffic, provide practical references for the planning and operation of urban underground transportation facilities, and help the core area realize the synergistic and sustainable development of transportation and space.